Pengaruh Disiplin Kerja terhadap Produktivitas Kerja Karyawan Asuransi Prudential di Kota Palangka Raya - Siren Siren; Erik Pranata (Pencerah Publik, 2015)
The research aims to understand how much the influence of work discipline has on employee productivity from Prudential City Palangka Raya employees. The research methods used in this study are quantitative research methods. Data collection in the form of observations and questionnaires. The data analysis technique in this study used the correlation analysis of the product moment according to Sugiyono (2012:212). The results concluded that the work discipline of Prudential insurance employees in the city of Palangka Raya is still lacking and not as expected. Judging from employees often come late, the salary received is improper, lack of appreciation, absence of written sanctions and lack of immediacy as Co-Office. Working discipline is very positive and significant towards the work productivity of insurance employees in the city Palangka Raya. From the results obtained by using the product correlation formula when the value is Rxy 0.995948.